The activity of erythropoietin as the pathogenetic component of anemia in acute myeloid leukemia - Lanovenko, I. I.; Berezyuk, O.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
During the investigation of the patients with acute myeloid leukemia (AML) under the conditions of intensive chemotherapy (CT), the development of anemia, the inadequacy of production, and the deficit of endogenic erythropoietin (EPO) are established. Insufficient production of EPO appeared in 80% of patients with AML before the conducting CT and in all patients after CT. A reduction in the production and the development of EPO insufficiency are accompanied by a deepening of anemia, disturbances of the metabolism of iron, and by an increase in the need for the pouring of erythrocytic mass. The pathogenetic role of the EPO insufficiency in the genesis of anemia is shown, and the expediency of erythropoietintherapy in sick AML is substantiated.